Adenocarcinoma of the Lung Presenting with Intrapulmonary Miliary Metastasis - Pillai, Saran (Cureus, 2019)
Miliary mottling on imaging is usually infectious in etiology and is less commonly seen with metastatic cancers. The cancers that are reported to cause miliary metastases include secondaries from cancers of the thyroid, kidney, trophoblasts, etc. Here, we report a case of a 63-year-old female who presented with prolonged cough and shortness of breath and whose imaging showed diffuse bilateral miliary nodules. Bronchoscopy with a transbronchial biopsy confirmed the diagnosis as adenocarcinoma of the lung with intrapulmonary miliary metastasis. Treatment with a combination of pemetrexed and carboplatin was not helpful and cancer had spread diffusely across the lung on repeat imaging after three months. It is essential to consider this clinical presentation as a separate subtype, with specific treatment protocols as compared to primary adenocarcinoma of the lung.